"Hybrid Governance, " Legitimacy, and (Il)legality in the Informal Cross-Border Trade in Panyimur, Northwest Uganda. (9th April 2014) - Titeca, Kristof; Flynn, Rachel
Abstract: By looking at a number of different commodities and how they are traded, this article shows how informal cross-border trade in West Nile and Panyimur, Uganda, is governed by a locally negotiated system of hybrid governance, in which neither state nor nonstate actors have a regulatory monopoly. Notions such as legality and illegality are secondary to the functioning of these hybrid institutions, which instead are the outcome of perceptions of the legitimacy of regulatory actions and trading practices and the power configurations of the actors involved. There are different "registers" at play about what constitutes legitimate economic action among different moral communities, but the actual impact of this system depends on the power of the strategic groups involved.